Advances in Cardiovascular Multimodality Imaging in Patients with Marfan Syndrome - Marco Alfonso Perrone; Sara Moscatelli; Giulia Guglielmi; Francesco Bianco; Deborah Cappelletti; Amedeo Pellizzon; Andrea Baggiano; Enrico Emilio Diviggiano; Maria Ricci; Pier Paolo Bassareo; Akshyaya Pradhan; Giulia Elena Mandoli; et al. (Diagnostics)
Marfan syndrome (MFS) is a genetic disorder affecting connective tissue, often leading to cardiovascular complications such as aortic aneurysms and mitral valve prolapse. Cardiovascular multimodality imaging plays a crucial role in the diagnosis, monitoring, and management of MFS patients. This review explores the advancements in echocardiography, cardiovascular magnetic resonance (CMR), cardiac computed tomography (CCT), and nuclear medicine techniques in MFS. Echocardiography remains the first-line tool, essential for assessing aortic root, mitral valve abnormalities, and cardiac function. CMR provides detailed anatomical and functional assessments without radiation exposure, making it ideal for long-term follow-up. CT offers high-resolution imaging of the aorta, crucial for surgical planning, despite its ionizing radiation. Emerging nuclear medicine techniques, though less common, show promise in evaluating myocardial involvement and inflammatory conditions. This review underscores the importance of a comprehensive imaging approach to improve outcomes and guide interventions in MFS patients. It also introduces novel aspects of multimodality approaches, emphasizing their impact on early detection and management of cardiovascular complications in MFS.